2018
DOI: 10.1093/cercor/bhy096
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Radial Glial Subtypes and Their Neurogenic Potential in Human Fetuses and Healthy and Alzheimer’s Disease Adults

Abstract: Neuropathological conditions might affect adult granulogenesis in the adult human dentate gyrus. However, radial glial cells (RGCs) have not been well characterized during human development and aging. We have previously described progenitor and neuronal layer establishment in the hippocampal pyramidal layer and dentate gyrus from embryonic life until mid-gestation. Here, we describe RGC subtypes in the hippocampus from 13 gestational weeks (GW) to mid-gestation and characterize their evolution and the dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 89 publications
9
103
1
Order By: Relevance
“…Cipriani et al (3)(4)(5), that there is absolute post childhood seize in formation of new neurons, though we support the notion that a significant proportion of the new formed cells in the neurogenic niche may be the glial cells. We conclude that an active but minimal hippocampal neurogenesis is possibly continued in adult human.…”
Section: Interpretations Of Our Data Advise Against the Conclusion Masupporting
confidence: 60%
See 2 more Smart Citations
“…Cipriani et al (3)(4)(5), that there is absolute post childhood seize in formation of new neurons, though we support the notion that a significant proportion of the new formed cells in the neurogenic niche may be the glial cells. We conclude that an active but minimal hippocampal neurogenesis is possibly continued in adult human.…”
Section: Interpretations Of Our Data Advise Against the Conclusion Masupporting
confidence: 60%
“…Studies with contrasting evidence have emerged since then which ranged from absolute denial (3)(4)(5) to approval for the persistence of AHN even in old individuals (6)(7)(8). In adult mammals (including human) neurogenesis is thought to persist in the subgranular zone (SGZ) of the dentate gyrus (DG) region of the hippocampus (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This understanding would be instrumental in designing targeted therapy options for AD in humans and may lead to more detailed analyses of NSC subtypes in experimental mammalian models of AD. Additionally, the role of Interleukin-4 and Serotonin in regulating diverse signaling mechanisms in NSCs opens up interesting research avenues as to whether modulation of neuroinflammatory milieu in mammalian brains would kick-start a "regeneration" response by mobilizing the endogenous reservoir of NSCs, which is a controversial subject (Arellano et al, 2018;Cipriani et al, 2018;Rodriguez and Verkhratsky, 2011;Sorrells et al, 2018;Tincer et al, 2016;Waldau and Shetty, 2008;Ziabreva et al, 2006). We propose that zebrafish can be used to address neurogenesis-related questions in disease conditions and could serve as a useful experimental model for investigating the molecular mechanisms of neural stem cell plasticity.…”
Section: Bdnf Expression Is Abundant In Mammalian Brainsmentioning
confidence: 99%
“…An alternative approach was suggested to be to complement the treatment in neuronal compartments with increasing the production of new neurons to provide resilience and strength to the diseased circuitry (Choi et al, 2018;Moreno-Jimenez et al, 2019;Mu and Gage, 2011;Tincer et al, 2016). Yet, neurogenesis in human brains is quite controversial (Arellano et al, 2018;Cipriani et al, 2018;Dennis et al, 2016;Duque and Spector, 2019;Sorrells et al, 2018). Although many reports documented the presence of adult neurogenesis in human brains (Boldrini et al, 2018;Ernst et al, 2014;Kempermann et al, 2018;Magnusson and Frisen, 2016;Moreno-Jimenez et al, 2019;Spalding et al, 2013), and several studies demonstrated that boosting the neurogenesis might be a viable option for alleviating the cognitive decline (Casse et al, 2018;Choi et al, 2018;Martinez-Canabal, 2014;Papadimitriou et al, 2018;Rodriguez and Verkhratsky, 2011), the potential benefits of neurogenic outcome in AD conditions requires further investigation and critical testing.…”
Section: Introductionmentioning
confidence: 99%